(untitled) (Research, Society and Development, 2021)
The present study aimed at the collaborative construction of a didactic model of the cardiovascular system of the human body associated with robotics, using the Arduino platform as a tool. This construction was carried out by students through a project at a state school in Água Doce, Maranhão. An investigative teaching sequence (SEI) was developed and the dialogues between students throughout the project were recorded through audio recordings. A questionnaire covering basic knowledge about the cardiovascular system was applied before and after the project and its data used to ascertain the evolution of learning through the Hake equation. The students developed the stages of the project in a participatory and committed manner, suggesting strategies and materials for building the model, which had the base made of expanded PVC and the cardiovascular system simulated by hoses and hydraulic pumps associated with a relay and ultrasonic sensor. SEI presented positive results in the development of learning about the cardiovascular system and, according to Hake’s equation, students presented an average learning gain. The students were able to collaboratively build the didactic model, associating it with robotics, as well as developing the programming language.